2017
DOI: 10.5604/15093492.1238002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes of Treatment with Resection Prosthesis of the Hip in Revision and Oncological Surgery

Abstract: 1.The use of the MUTARS modular resection prosthesis allows for fast clinical improvement that meets the patient's expectations both in oncological treatment and in revision arthroplasty. 2. The extent of bone resection, procedure duration and perioperative blood loss associated with the surgical placement of a resection prosthesis are similar in oncological treatment and in revision arthroplasty. 3. The use of a resection prosthesis in revision arthroplasty is associated with a high risk of implant dislocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We reported the Musculoskeletal Tumor Society (MSTS) score to assess functional outcome as it was most commonly reported (23 studies reported the MSTS score). Only two studies reported the Toronto Extremity Salvage score, and six studies reported the Harris Hip score . The MSTS score is a clinician completed assessment rating six domains, resulting in a score of 0 to 100%, with a higher score indicating better function …”
Section: Methodsmentioning
confidence: 99%
“…We reported the Musculoskeletal Tumor Society (MSTS) score to assess functional outcome as it was most commonly reported (23 studies reported the MSTS score). Only two studies reported the Toronto Extremity Salvage score, and six studies reported the Harris Hip score . The MSTS score is a clinician completed assessment rating six domains, resulting in a score of 0 to 100%, with a higher score indicating better function …”
Section: Methodsmentioning
confidence: 99%
“…In our review we included 10 full-text articles [1-4,6-10,12] and 2 papers [5,11] evaluated by title and abstract. The studies we selected were: eight retrospectives [1,2,4-8] and five prospective [3,[9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Females are more represented than males in the considered papers, contrary to major epidemiological data. The types of bone tumors included in the studies are disparate, both in histological terms and primary or secondary nature: four papers [2,4,9,11] analyze only primary tumors, two articles study only metastatic lesions [5,8], while most studies collect data regarding both primary and secondary bone lesions [1,3,12]and the remaining articles don't report these informations [6,7,10]. Histological tumors reported are: metastatic bone tumors, osteosarcoma, leiomyosarcoma, chondrosarcoma, giant cell tumors, lymphomas and other primary bone tumors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations